(3aJM GdeZjKs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s; (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef GdYQGbj, Rjf GdOjf,J (B806 (3g` s ((3eMeO Hf Ydi Hf eMeOGdMSjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bHd HUMjM GdfjI MSf GdYed hHYO , aYde GdMOjK NWjQ hcfJ fXeJ ajg CQLhRI CdaJgG hTQYJ ai TQM dgG HSWg hChVMJg Ke QCjJg cKjQ GdMLe Ke TQYJ ai TQM eJhSW s
(3BNQgG (B:s
(3ajbhd GdTGei GdOeTbi GdOGQi hcedJ HWjHg Gdejehfg aHQRJ ef MPQgG eUhfg hced gPG GdTQM YdjgG ai jhe GdSHJ GdJGSY hGdYTQjf ef TghQ QeVGf SfI EMOi hSHYjf hSHYeGFI HGdNGfbGg GdWTJeQjI hGdMeO ddg Ydi fYeg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344s
Keywords: (3GdMOjK h GdeUWdMs